Effect of a Short-Term Low Glycemic Index Dietary Intervention on Ad Libitum Food Intake, Diet Quality, and Subjective Appetite Ratings in Preschoolers. (14th June 2022) - Hasan, Faten; Gaylinn, Bruce; Malin, Steven; Weltman, Arthur; Angadi, Siddhartha; Patrie, James; Kranz, Sibylle
Abstract: Objectives: To examine the effect of ad-libitum low-glycemic index (GI; high fiber) versus high-GI diet on energy intake, diet quality (Healthy Eating Index 2015 (HEI-2015)), self-reported feelings of hunger and fullness, liking of the foods, and physical activity (PA) in preschoolers. Methods: Twenty-five healthy preschoolers (aged 48 ± 7.3 mo, 47% females, 73% healthy weight) were recruited to participate in "day camps" of two low- and two high-GI (usual diet) days. Food and nutrient consumption, HEI-2015 scores, pre- and post-lunch hunger ratings, food liking, and PA were measured each day. Paired t-tests were used to compare treatment differences. Results were stratified into healthy (HW; <85% of BMI-for Age z-score of the CDC growth charts) and non-healthy weight (NHW; ≥85%) and compared within- (by diet) and between- (HW vs NHW) groups. Results: GI and glycemic load (GL) were significantly lower on the low- versus high- GI diet (GI: 46.5 ± 3.3 vs 58.2 ± 5.1, GL: 24.9 ± 16.8 vs 47.4 ± 17.9, respectively; P < 0.01). Children consumed more total fiber while eating the low-GI diet (14.6 ± 8.8g vs 6.4 ± 2.6, P < 0.001), despite no difference between low- and high-GI diets in total energy (459.3 ± 230.6 vs 497.5 ± 173.9kcal, p< 0.001), carbohydrate (82.9 ± 45.1 vs 87.4 ± 30.9g, p = 0.55), fat (10.5 ± 5.2 vs 12.3 ± 5.7g, p = 0.07), and protein (14.4 ± 8.4 vs 12.0 ± 5.1, p = 0.05) intake, respectively. Mean HEI-2015 scores were higher on the low- versus high-GI diets (85.2 ± 11.6 and 59.4 ± 7.0, respectively; P < 0.001). There were no differences in hunger (p > 0.26), food liking (p > 0.01), or PA (p = 0.88) between diets. Fewer NHW children reported being "full" compared to HW children, (26% vs 52%, respectively, p = 0.03), yet both groups had similar energy intake (467.5 ± 155.0 and 482.1 ± 220.7kcal, respectively, p = 0.78). Conclusions: An ad libitum low-GI diet provided better diet quality in preschoolers, with no difference in food liking. Although there was no effect on hunger, body mass may influence response to food intake and suggests eating in the absence of hunger observed in the overweight/obese children. Additional work is needed to better understand the effect of low-GI diets and fiber consumption on appetite regulation in preschoolers with overweight/obesity. Funding Sources: This study was funded by the University of Virginia School of Education and Human Development Initiative Fund.